2007
DOI: 10.1523/jneurosci.3162-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Spatial Attention on Contrast Response Functions in Human Visual Cortex: Figure 1.

Abstract: Previous electrophysiology data suggests that the modulation of neuronal firing by spatial attention depends on stimulus contrast, which has been described using either a multiplicative gain or a contrast-gain model. Here we measured the effect of spatial attention on contrast responses in humans using functional MRI. To our surprise, we found that the modulation of blood oxygenation level-dependent (BOLD) responses by spatial attention does not greatly depend on stimulus contrast in visual cortical areas test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
182
4
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(223 citation statements)
references
References 27 publications
35
182
4
2
Order By: Relevance
“…This is supported by the recent finding that spatial attention adds a constant BOLD signal independent of stimulus strength in V1 (Buracas and Boynton, 2007). Because stimulus onsets attract attention, such a hemodynamic effect might explain the temporal nonlinearities observed in most fMRI studies, in which responses to brief auditory and visual stimuli are much larger than expected from the responses to stimuli of longer durations (Birn et al, 2001).…”
Section: Discussionmentioning
confidence: 68%
“…This is supported by the recent finding that spatial attention adds a constant BOLD signal independent of stimulus strength in V1 (Buracas and Boynton, 2007). Because stimulus onsets attract attention, such a hemodynamic effect might explain the temporal nonlinearities observed in most fMRI studies, in which responses to brief auditory and visual stimuli are much larger than expected from the responses to stimuli of longer durations (Birn et al, 2001).…”
Section: Discussionmentioning
confidence: 68%
“…Two studies have reported results supporting both (Huang and Dobkins 2005;Ling and Carrasco 2006). Functional imaging studies found evidence supporting an additive effect of attention (Buracas and Boynton 2007) (Ekstrom et al 2009). These results are important in their own right, but they provide little guidance for anticipating the effects of attention on the firing rates of individual neurons.…”
Section: Psychophysics and Imagingmentioning
confidence: 99%
“…In humans, some fMRI studies have described contrastindependent attentional modulation of BOLD signals in visual cortex (Buracas and Boynton, 2007;Murray, 2008), while others have reported contrast-dependent modulations (Li et al, 2008; see also Ekstrom et al, 2009 in the monkey). Behavioral studies have also described both modulation types of psychometric functions (Carrasco, 2006).…”
Section: Introductionmentioning
confidence: 99%